Implementation of state-dependent plasticity model in strain wedge model for laterally loaded piles in sand. Issue 5 (28th May 2019) - Xu, Ling-Yu; Cai, Fei; Xue, Ying-Ying
ABSTRACT: The strain wedge model effectively performs nonlinear analyses of the lateral response of piles by using a nonlinear stress-strain relationship to describe soil behavior in the strain wedge. In this study, a state-dependent plasticity model has been implemented in the strain wedge model to calculate the stress-strain relationship for sand in the strain wedge. To complement this implementation, the effect of dilatancy on the shear strain is considered in the strain wedge. A full-scale test and a 45 g centrifuge model test on laterally loaded piles are used to validate the proposed method. The results show that the deflections and moments predicted by the proposed method accord well with those measured from full-scale and centrifugal model pile tests. Moreover, the combination of the state-dependent plasticity model and the strain wedge model allows for analyzing the lateral response of single piles using a unique set of model parameters for different relative densities of sands. In addtion, the stress-strain response in the strain wedge, not the dilatancy, dominates the soil resistance in the strain wedge and thus the lateral response of piles.